The Impact of Corporate and Personal Income Taxes on the Location of Firms and on Employment: Some Panel Evidence for the Swiss Cantons - Lars P. Feld; Gebhard Kirchgässner (Center for Economic Studies and ifo Institute (CESifo), 2001)
The impact of corporate income taxes on location decisions of firms is widely debated in the tax competition literature. Tax rate differences across jurisdictions may lead to distortions of firms' investment decisions. Empirical evidence on tax induced relocation and subsequent economic development in the U.S. and Europe is still inconclusive. Much the same applies to Switzerland. While there is some evidence on personal income tax competition between Swiss cantons, evidence on the impact of intercantonal corporate income tax differences on the location of business within Switzerland is missing. In this paper, we present econometric evidence on the influence of corporate and personal income taxes on the regional distribution of firms in 1981 and 1991 and on cantonal employment using a panel data set of the 26 Swiss cantons from 1985 to 1997. The results show that corporate and personal income taxes deter firms to locate in a canton and subsequently reduce cantonal employment.
Keywords: 330; Corporate income taxes; personal income taxes; tax competition; business location